MATLAB Programming of Nonlinear Equations of Ordinary Differential Equations and Partial Differential Equations - Balamuralitharan, S.; ., . (International Journal of Engineering and Technology, 2018)
My idea of this paper is to discuss the MATLAB program for various mathematical modeling in ordinary differential equations (ODEs) and partial differential equations (PDEs). Idea of this paper is very useful to research scholars, faculty members and all other fields like engineering and biology. Also we get easily to find the numerical solutions from this program.Â Â